The Role of Ultrasonography in the Discrimination of Reactive Lymphadenopathy in Children - Elif Şeker Ekici; Mustafa Büyükavcı; Yasemin Gündüz; Mehmet Fatih Orhan; Bahri Elmas (Güncel Pediatri)
Introduction: Many studies have been conducted on the role of ultrasonography in differentiating benign diseases that cause lymphadenopathy (LAP) from malignant diseases. However, there are no studies to distinguish LAP due to reactive etiologies from other benign infectious causes. In this study, the role of ultrasonography in the differentiation of benign LAPs was examined. Materials and Methods: This study prospectively evaluated 165 children with LAP aged 0-18 years. According to their clinical features, benign LAPs were grouped into viral and bacterial lymphadenitis, and reactive LAPs. Ultrasonographic characteristics of each group were assessed. Results: While loss of hilar echogenicity from ultrasonographic findings of LAPs was significant in differentiating reactive LAP from viral lymphadenitis, border irregularity was more favorable for bacterial lymphadenitis. Conclusion: Differentiating benign LAPs is important in the decision to prescribe antibiotics. In addition to the clinical features, ultrasonographic features can also be used to make this distinction.